Sensing sonically at Andean Formative Chavín de Huántar, Perú. (2nd January 2017) - Kolar, Miriam A.
ABSTRACT: Archaeoacoustics operationalizes non-verbal sound as means and medium for communication. In reconstructing physical, environmental features of ancient places, we infer their consistent sensory reception across the six-digit timeline of Homo sapiens, yet cognition is contextual. How can we reasonably estimate ancient sonic experiences in prehistoric archaeology? Is it possible to infer the significance of sound for past humans who have left no textual traces? Systematic auditory localization experimentation and other archaeoacoustics research within the extant architecture of the Andean Formative ceremonial center at Chavín de Huántar, Perú has demonstrated specific ways in which ancient built acoustics transform humans' understandings of place and social relations. Transposing principles from information theory to explore the structuring of Chavín's sonic environment, I argue that sonic symbols that parallel in-situ visual depictions are architecturally encoded at Chavín, constituting multi-channel messaging. For example, the plausible evocation of a roaring cayman through hydraulic-sonic enactment of Chavín's so-called 'acoustic canal' creates a sonic incarnation of that visually depicted crocodilian. Chavín symbols, delivered redundantly and repetitively via multiple, simultaneous sensory channels, would ensure assimilation by ritual participants. If, as evidence suggests, Chavín drew visitors from diverse polities, messaging to a multi-lingual population would necessitate non-linguistic communication, through sensory manipulation in its unique 'ritualscape'.